Clifford counts 1 2 3 - Bridwell, Norman (New York : Scholastic, 1998)
Clifford counts to three using houses, trees, cars, airplanes, trucks, and children.
Cover title.
On board pages.
"Cartwheel books"--Cover p. [4].
1.7
K-3
K-3
Keywords: Clifford (Fictitious character : Bridwell) -- Fiction; Dogs -- Fiction; Counting; Clifford (Fictional character : Bridwell) -- Fiction; Dogs -- Fiction; Counting